2017
DOI: 10.11152/mu-1027
|View full text |Cite
|
Sign up to set email alerts
|

Performance of lung ultrasonography for the diagnosis of communityacquired pneumonia in hospitalized children

Abstract: Aims: The objective of the study was to assess the performance of lung ultrasonography (LUS) as compared to chest radiography and the clinical criteria for the diagnosis of pneumonia in children.Materials and methods: This was a retrospective study in which data were collected from medical files of 81 children admitted with a clinical suspicion of pneumonia in which both an LUS and a chest radiograph during the hospitalization were performed. Reference standard used for the diagnosis of pneumonia were chest ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Eighteen prospective cohort studies, five retrospective cohort studies, one randomized controlled trial, and one case‐control study were included. Three studies were conducted in North America, one in South America, in Europe,, five in Asia, and one in both South American and Asia . Study subjects were mostly infants, children, and adolescents except for two studies that included neonates .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen prospective cohort studies, five retrospective cohort studies, one randomized controlled trial, and one case‐control study were included. Three studies were conducted in North America, one in South America, in Europe,, five in Asia, and one in both South American and Asia . Study subjects were mostly infants, children, and adolescents except for two studies that included neonates .…”
Section: Resultsmentioning
confidence: 99%
“…The LUS training novice sonographers received varied greatly, ranging from 1 hour to the a priori–defined cutoff of 7 days of training . Ten studies were carried out in the ED and 13 in an inpatient setting with four in the ICU and nine in the ward . High‐frequency linear transducers (5–10 MHz) were most frequently utilized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and specificity of 44%-100%). 8,10,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] On the contrary, our study focused on novel aspects. LUS allows the detailed description of lung pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated diagnostic accuracy with sensitivities ranging from 40% to 100% and specificities ranging from 44% to 100%. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Despite these variations in sensitivities and specificities, recent studies 31 and metanalyses 24 have shown very promising results on lung US accuracy.…”
Section: Discussionmentioning
confidence: 99%